An acute bout of whole-body vibration on skeleton start and 30-m sprint performance - Bullock, N.; Martin, D. T.; Ross, A.; Rosemond, D.; Jordan. M. J.; Marino, F. E. (European Journal of Sport Science, 2009)
Maximal 30-m upright sprinting and bent over, skeleton push performance were examined in five female national team skeleton athletes before and 10 min after an acute bout of whole-body vibration or no vibration. The whole-body vibration was applied at a frequency of 45 Hz with 4-mm displacement for 31-min treatments separated by 1 min. All changes in 30-m sprint and skeleton push times before and after whole-body vibration were small or trivial and within the tests' typical variation (~3.7% for the skeleton push and ~3.2% for the upright sprint). Athletes were able to achieve 75-79% of their 30-m upright sprinting velocities when pushing a skeleton sled. These results question the effectiveness of whole-body vibration as an ergogenic aid immediately before performing a maximal upright sprint or skeleton push following a comprehensive warm-up.